Organochlorine chemicals and neurodegeneration among elderly subjects in Costa Rica - Steenland, K.; Mora, A.M.; Barr, D.B.; Juncos, J.; Roman, N.; Wesseling, C. (ENVIRONMENTAL RESEARCH, 2014)
We previously screened 400 elderly Costa Ricans for neurodegenerative disease. Those reporting occupational pesticide exposure (18%) had an increased Parkinson׳s disease (PD) risk (OR 2.57, 95% CI 0.91–7.26), and worse cognition (Mini-Mental States Exam (MMSE) 24.5 versus 25.9 points, p=0.01). We subsequently measured long-lasting organochlorine pesticides (β-HCH, DDE, DDT, and dieldrin) in a sub-sample (n=89). Dieldrin and β-HCH have been linked to PD, and DDE to Alzheimer׳s disease. We ran regression models for MMSE and tremor-at-rest to assess associations with pesticides in 89 subjects. The percent of β-HCH, DDE, DDT (parent compound for DDE), and dieldrin above their limit of detection (LOD) were 100%, 93%, 75%, and 57%, respectively. Tremor-at-rest was found in 21 subjects, and the mean MMSE was 25. Those who reported occupational pesticide exposure (n=36) had more detectable dieldrin samples (p=0.005), and higher mean levels of dieldrin (p=0.01), than those not reporting exposure. Other pesticides did not differ between those with and without self-reported occupational exposure. There was a positive but non-significant trend of higher risk for tremor-at-rest with higher dieldrin (p=0.10 for linear trend). Neither DDE nor DDT showed a relationship with MMSE. However, after excluding two outliers with the lowest MMSE scores, higher DDT levels showed some modest association with lower MMSE (p=0.09 for linear trend). Our data are limited by small sample size. However, dieldrin was high in our population, has been previously linked to PD, and could be partly responsible for the excess PD risk seen in our population. •We previously found excess Parkinson׳s disease (PD) in 400 elderly Costa Ricans•Those reporting occupational pesticide exposure had 2–3 fold excess risk of PD.•We measured 4 organochlorine pesticides in a sub-sample (n=89) of these subjects.•Dieldrin, previously associated with PD, was found at high levels in the sub-sample.•There was some evidence that higher dieldrin was associated with increased tremor.